Knowledge and perceptions of diabetes in a semi-urban Omani population - Ganguly Shyam S; Khan Mushtaq A; Al Farsi Yahya; Rizvi Syed; Al-Shukaili Sulaiman; Al Shafaee Mohammed A; Afifi Mustafa; Al Adawi Samir (BMC, 2008)
Abstract Background Diabetes mellitus is a major public health problem in the Sultanate of Oman. This study aimed to evaluate the knowledge and perception of diabetes in a sample of the Omani general population, and the associations between the elements of knowledge and perception, and socio-demographic factors. Methods The study was carried out in two semi-urban localities. A total of 563 adult residents were interviewed, using a questionnaire specifically designed for the present study. In addition to demographic information, the questionnaire contained questions on knowledge related to diabetes definition, symptoms, risk factors, complications and preventative measures, as well as risk perception for diabetes. Results Knowledge of diabetes was suboptimal. The percentages of correct responses to questions on diabetes definition, classical symptoms, and complications were 46.5%, 57.0%, and 55.1%, respectively. Only 29.5%, 20.8% and 16.9% identified obesity, physical inactivity and a positive family history, respectively, as risk factors for diabetes. A higher level of education, a higher household income, and the presence of a family history of diabetes were found to be positively associated with more knowledge. Conclusion This study demonstrated that there is lack of awareness of major risk factors for diabetes mellitus. Level of education is the most significant predictor of knowledge regarding risk factors, complications and the prevention of diabetes. Given that the prevalence of diabetes has increased drastically in Oman over the last decade, health promotion seems essential, along with other means to prevent and control this emerging health problem.